2016
DOI: 10.1093/mnras/stw969
|View full text |Cite
|
Sign up to set email alerts
|

Low-mass neutron stars: universal relations, the nuclear symmetry energy and gravitational radiation

Abstract: The lowest neutron star masses currently measured are in the range 1.0 − 1.1 M ⊙ , but these measurement have either large uncertainties or refer to isolated neutron stars. The recent claim of a precisely measured mass M/M ⊙ = 1.174±0.004 (Martinez et al. 2015) in a double neutron star system suggests that low-mass neutron stars may be an interesting target for gravitational-wave detectors. Furthermore, Sotani et al. (2014) recently found empirical formulas relating the mass and surface redshift of nonrotating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 128 publications
(193 reference statements)
2
42
0
Order By: Relevance
“…Here we consider the following multiplicative combinations for comparison purposes: K 0 L η 0 , M 0 L µ 0 , and K sym,0 L ν 0 , where coefficients η, µ, and ν are similarly chosen to achieve maximal correlation. Such multiplicative combinations are similar to those considered in [30,31]. Figure 14 presents the correlations betweenΛ and all 6 multiplicative and linear combinations of nuclear parameters considered in this analysis.…”
Section: Appendix B: Multiplicative Combinations Of Nuclear Parameterssupporting
confidence: 55%
“…Here we consider the following multiplicative combinations for comparison purposes: K 0 L η 0 , M 0 L µ 0 , and K sym,0 L ν 0 , where coefficients η, µ, and ν are similarly chosen to achieve maximal correlation. Such multiplicative combinations are similar to those considered in [30,31]. Figure 14 presents the correlations betweenΛ and all 6 multiplicative and linear combinations of nuclear parameters considered in this analysis.…”
Section: Appendix B: Multiplicative Combinations Of Nuclear Parameterssupporting
confidence: 55%
“…Additionally shown in dotted blue are the corresponding bounds on M0 and Ksym,0 computed by Ref. [11], using priors ofΛ ∈ [70,720] and L0 ∈ [30,86] MeV. Observe how the results for the 90% confidence intervals obtained in this section are slightly smaller than those found in Sec.…”
Section: Conclusion and Discussionmentioning
confidence: 61%
“…Interestingly, approximate universal relations exist among nuclear physics parameters mentioned above and NS radius at a given mass [28] (see e.g. [29,30] for other universal relations involving nuclear parameters). The authors found that while individual nuclear parameters are only weakly correlated with the stellar radius, linear combinations of the form K 0 + αL 0 and M 0 + βL 0 become highly correlated, where α and β are chosen such that the correlation becomes maximum.…”
Section: Introductionmentioning
confidence: 99%
“…(4) and (5)], while the dashed lines are plotted with using Eqs. (6) - (9). Now, I can get the fitting formulae expressing the maximum mass and radius of neutron star with maximum mass as a function of η and α.…”
Section: Possible Maximum Massmentioning
confidence: 99%
“…In particular, the nuclear saturation parameters are important for expressing lower density region. It is practically known that the neutron star constructed with the central density lower than 2ρ 0 can be described nicely with parameters constructed as the combination of the incompressibility of the symmetric nuclear matter, K 0 , and the so-called slope parameter of nuclear symmetry energy, L, via η = (K 0 L 2 ) 1/3 [8,9]. Therefore, it is expected that the maximum mass of neutron stars should also depend on η, where η has been already constrained in some range via the constraints on K 0 and L [10][11][12] and will be further constrained in the future.…”
Section: Introductionmentioning
confidence: 99%